2022
DOI: 10.18192/aporia.v14i2.6424
|View full text |Cite
|
Sign up to set email alerts
|

Nurses and the Discursive Construction of Procedural Justice in Review Board Hearings

Abstract: There has been growing interest about procedural justice in mental health tribunals. A process considered procedurally just increases adherence to treatment, increases compliance with judicial decisions and allows efficient community reintegration. Yet, little is known about how procedural justice is carried out and the role of professionals in its implementation. Stemming from the results of a critical ethnography of the Ontario Review Board, in this article we examine how procedural justice materializes duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This approach actually ampli es the objective injustice of the process, as the authority uses the principle of voice to advance its own interests (34). A study on the unfolding of mental health review board hearings in Canada revealed that procedural justice was used as a way to give the illusion to the patients that their voices were being heard, while what was said was very rarely taken into consideration (41). In the eld of mental health, although the principles of autonomy and reciprocity are often highlighted in the literature, paternalism remains predominant in practice (42).…”
Section: Voicementioning
confidence: 99%
“…This approach actually ampli es the objective injustice of the process, as the authority uses the principle of voice to advance its own interests (34). A study on the unfolding of mental health review board hearings in Canada revealed that procedural justice was used as a way to give the illusion to the patients that their voices were being heard, while what was said was very rarely taken into consideration (41). In the eld of mental health, although the principles of autonomy and reciprocity are often highlighted in the literature, paternalism remains predominant in practice (42).…”
Section: Voicementioning
confidence: 99%
“…An interview conducted with one forensic psychiatric nurse exemplifies particularly well the dynamic of surplus obedience in a system that is known to be harmful. This nurse identified injustices inherent to ORB hearings in that he perceived ORB hearings to be mere ‘formalities’ intended to provide a ‘sense importance’ for persons NCR, instead of the high‐stake inquiries they are (Domingue et al, 2022, p. 15). Yet, this same nurse went above‐and‐beyond their required professional responsibilities to ensure the ORB hearing machine ran smoothly.…”
Section: Surplus Obedience As a Foundation Of Organisational Sustaina...mentioning
confidence: 99%
“…Despite being non-adversarial inquisitive hearings (Criminal Code, 1985), the spatial distribution of participants during RB hearings and the processes inherent to them were reminiscent of criminal trials. A full description and analysis of the spatiotemporal particularities of the observed RB hearings are discussed elsewhere (Domingue et al, 2020(Domingue et al, , 2022.…”
Section: Observations Of Rb Hearingsmentioning
confidence: 99%